Understanding the Immune-Stroma Microenvironment in B Cell Malignancies for Effective Immunotherapy - Apollonio, Benedetta; Ioannou, Nikolaos; Papazoglou, Despoina; Ramsay, Alan G. (Frontiers in Oncology, 2021)
Cancers, including lymphomas, develop in complex tissue environments where malignant cells actively promote the creation of a pro-tumoral niche that suppresses effective anti-tumor effector T cell responses. Research is revealing that the tumor microenvironment (TME) differs between different types of lymphoma, covering inflamed environments, as exemplified by Hodgkin lymphoma, to noninflamed TMEs as seen in chronic lymphocytic leukemia (CLL) or diffuse-large B-cell lymphoma (DLBCL). In this review we consider how T cells and interferon-driven inflammatory signaling contribute to the regulation of anti-tumor immune responses as well as sensitivity to anti-PD-1 immune checkpoint blockade immunotherapy. We discuss tumor intrinsic and extrinsic mechanisms critical to anti-tumor immune responses, as well as sensitivity to immunotherapies, before adding an additional layer of complexity within the TME: the immunoregulatory role of non-hematopoietic stromal cells that co-evolve with tumors. Studying the intricate interactions between the immune-stroma TME in lymphoma should help to design next-generation immunotherapies and combination treatment strategies to overcome complex TME-driven immune suppression.